Barrier Packaging Materials
The barrier film with a polyolefin resin base and deformation-resistant coat layer addresses the challenge of monomaterialization by ensuring high gas barrier properties and abuse resistance, facilitating efficient recycling and reducing environmental impact.
Patent Information
- Application Number
- JP2021539838
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-09
- Filing Date
- 2020-07-02
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-07-02
AI Technical Summary
Existing flexible packaging materials face challenges in achieving monomaterialization while maintaining high gas barrier properties and abuse resistance, particularly during manufacturing and distribution processes.
A barrier film comprising a polyolefin resin base film with an inorganic oxide layer and a deformation-resistant barrier coat layer containing a hydroxyl group-containing polymer compound and water-swellable mica, which allows the layer to follow the deformation of the base film, ensuring excellent gas barrier properties and abuse resistance.
The solution enables monomaterial packaging materials with superior recyclability and abuse resistance, maintaining gas barrier properties even under deformation, thus enhancing the efficiency of plastic recycling and reducing environmental impact.
Smart Images

Figure 0007605112000006 
Figure 0007605112000007 
Figure 0007605112000008
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a gas barrier film that can be used in a packaging material to restrict water vapor and / or oxygen. The packaging material is for packaging food such as dried food, confectionery, bread, delicacies, etc., or medicines such as tablets, powdered medicines, poultices, and patches (of course, other items can also be packaged). More specifically, the present disclosure relates to a barrier film used in the packaging field for applications that have high gas barrier properties and transparency that allows visual confirmation of the contents. The present disclosure also relates to a packaging material that includes this barrier film. [Background technology]
[0002] Resin films are used to package food and other contents. For example, Patent Document 1 discloses a barrier film for packaging food. Patent Document 2 discloses a film in which a metal or metal oxide layer is laminated on a polyethylene film. Patent Document 3 discloses a gas barrier film comprising a base film and a coating layer containing a water-soluble polymer and water-swellable mica. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] U.S. Pat. No. 10,066,093 [Patent Document 2] US Patent Publication No. 2016 / 0039181 [Patent Document 3] International Publication No. 2019 / 088265 Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, due to the heightened environmental awareness triggered by the problem of marine plastic waste, etc., there is a demand for further improved efficiency in the sorting and recovery of plastic materials and their recycling. In other words, even for soft packaging materials, which have traditionally been made high-performance by combining various different materials, there is a demand for them to be made into mono-materials. However, when attempting to make soft packaging materials into mono-materials by using polyolefin resins, the reality is that it is difficult to obtain good barrier properties.
[0005] For example, soft packaging materials containing products are bent during the manufacturing and distribution process, and soft packaging materials rub against each other. Even after such processes, the soft packaging materials need to maintain their gas barrier properties. This property required of packaging materials is referred to as "abuse resistance" in this specification. The present inventors have found that in order to achieve excellent abuse resistance of a barrier film, it is useful to adjust the softness of the barrier coat layer so that the barrier coat layer can sufficiently follow the deformation of the base film, that is, to impart deformation resistance to the barrier coat layer.
[0006] The present disclosure provides barrier films and barrier packaging materials that are useful for achieving excellent recyclability of the packaging materials and have excellent abuse resistance. [Means for solving the problem]
[0007] The barrier film according to the first aspect of the present disclosure comprises a substrate film containing a polyolefin resin, an inorganic oxide layer provided on one side of the substrate film, and a deformation-resistant barrier coat layer provided on and in contact with the inorganic oxide layer, the deformation-resistant barrier coat layer containing a hydroxyl group-containing polymer compound and water-swellable mica, and the content of the water-swellable mica in the deformation-resistant barrier coat layer is 5 parts by mass to 35 parts by mass when the total mass of the deformation-resistant barrier coat layer is 100 parts by mass.
[0008] In the barrier film according to the first aspect, the inorganic oxide layer and the deformation-resistant barrier coat layer function as a barrier layer, and exhibit excellent gas barrier properties. Since the deformation-resistant barrier coat layer has a water-swellable mica content in the above range, the deformation-resistant barrier coat layer can follow the deformation of the base film, and therefore the inorganic oxide layer provided on the surface of the deformation-resistant barrier coat layer can be stably protected. Therefore, the barrier film has excellent abuse resistance.
[0009] According to the barrier film of the first embodiment, since the base film contains a polyolefin resin, it is possible to realize a mono-material packaging material by using the base film in combination with a sealant layer containing a polyolefin resin. In the present disclosure, a mono-material packaging material refers to a packaging material in which the mass ratio of a specific material (e.g., a polyolefin resin) is 90 mass% or more.
[0010] The barrier film according to the second aspect of the present disclosure is a laminated film including a substrate film containing polyethylene and a deformation-resistant barrier coat layer containing a hydroxyl group-containing polymer compound. With this barrier film, the deformation-resistant barrier coat layer functions as a barrier layer, and exhibits excellent gas barrier properties. Since the deformation-resistant barrier coat layer can follow the deformation of the substrate film, it has excellent abuse resistance. In addition, with this barrier film, since the substrate film contains polyethylene, it is possible to realize a mono-material packaging material by using it in combination with a sealant layer containing polyethylene.
[0011] A barrier packaging material according to one aspect of the present disclosure comprises the barrier film according to the first or second aspect and a sealant layer containing a polyolefin resin. From the viewpoint of realizing mono-materialization, the sealant layer is preferably made of the same plastic material as the base film. For example, when the base film is a polyethylene film, the sealant layer is preferably a polyethylene film, and when the base film is a polypropylene film, the sealant layer is preferably a polypropylene film. polypropylene The ink layer is preferably provided on, for example, a deformation-resistant barrier coat layer of the barrier film. Effect of the Invention
[0012] The present disclosure provides barrier films and barrier packaging materials that are useful for achieving good recyclability of the packaging material and have good abuse resistance. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic configuration of a barrier film according to a first embodiment of the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic configuration of a barrier film according to a second embodiment of the present disclosure. [Diagram 3] FIG. 3 is a cross-sectional view that illustrates a schematic configuration of a barrier film according to a third embodiment of the present disclosure. [Figure 4] FIG. 4 is a cross-sectional view that illustrates a schematic configuration of a barrier film according to a fourth embodiment of the present disclosure. [Diagram 5] FIG. 5 is a cross-sectional view illustrating a schematic configuration of a packaging material according to an embodiment of the present disclosure. [Figure 6] FIG. 6 is a diagram for explaining a method for measuring the thermal shrinkage rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The embodiments of the present disclosure are described below. The present invention is not necessarily limited to the following embodiments. These embodiments are illustrative, and a person skilled in the art can understand how to implement the present invention in a manner other than that described below. In the following description, the same elements or elements having the same functions are designated by the same reference numerals, and duplicated descriptions are omitted.
[0015] <Barrier film> [First embodiment] Fig. 1 is a cross-sectional view showing a schematic configuration of a barrier film according to a first embodiment. The barrier film 10A shown in this figure comprises a substrate film 1 containing at least polyethylene, and a deformation-resistant barrier coat layer 3A as a barrier layer provided on one surface of the substrate film. The deformation-resistant barrier coat layer 3A contains at least a hydroxyl group-containing polymer compound.
[0016] The base film 1 is a plastic film containing polyethylene, for example, a material containing 50% or more of polyethylene. Polyethylene means a homopolymer of ethylene or a copolymer of ethylene and 5 mol% or less of an α-olefin monomer. Resin materials other than polyethylene can be mixed as long as the possibility of recycling as at least polyethylene resin is not excluded. The base film 1 is preferably a material that can be recycled as polyethylene. The base film 1 may contain polyethylene derived from biomass or recycled products. Although the case where the base film 1 is a polyethylene film is illustrated here, the base film 1 may be an olefin-based resin film other than polyethylene.
[0017] As the polyethylene, for example, those classified as low density polyethylene (LDPE), medium density polyethylene (MDPE), and high density polyethylene (HDPE) can be used. LDPE is a polyethylene with a density of 0.910 g / cm 3 Above 0.925g / cm 3 The following polyethylene: MDPE has a density of 0.926 g / cm 3 Above 0.940g / cm 3 The following polyethylene: HDPE has a density of 0.941 g / cm 3 Above 0.965g / cm 3 The following polyethylenes are available. LDPE is obtained by polymerizing ethylene at a high pressure, for example, from 1000 atm to less than 2000 atm. MDPE and HDPE are obtained by polymerizing ethylene at a medium or low pressure, for example, from 1 atm to less than 1000 atm. MDPE and HDPE may partially contain a copolymer of ethylene and an α-olefin.
[0018] An example of a copolymer of ethylene and an α-olefin is linear low density polyethylene (hereinafter also referred to as LLDPE). LLDPE is obtained by copolymerizing an α-olefin with a linear polymer obtained by polymerizing ethylene at medium or low pressure to introduce short chain branches. Examples of α-olefins include butene-1, hexene-1, 4-methylpentene, and octene-1. The density of LLDPE is, for example, 0.915 g / cm. 3 Above 0.945g / cm 3 The following is the result.
[0019] The base film 1 may be a single layer film or a multilayer film. From the viewpoint of heat resistance, a single layer film of HDPE may be used, or HDPE may be used for the thickest core layer constituting the base film 1. In addition, it may contain additives such as antioxidants, lubricants, antiblocking agents, and neutralizing agents. In the case of a multilayer base film, for example, the layer on the side where the barrier layer is laminated may not contain a lubricant.
[0020] In order to suppress deterioration of the barrier layer due to thermal deformation, the base film 1 is formed in a first direction on the film plane and in a direction perpendicular to the first direction. Exchange In the second direction perpendicular to the first direction, the thermal shrinkage rate at 100° C. for 15 minutes may be 2% or less. Exchange The second direction is, for example, MD (resin flow direction) or TD (vertical direction). In addition, the heat shrinkage rate at 120°C for 15 minutes may be 5% or less, and the heat shrinkage rate at 80°C for 15 minutes may be 1% or less.
[0021] The base film 1 may be an unstretched film, a uniaxially stretched or biaxially stretched oriented film, or a film that has been surface-treated (such as corona discharge treatment) or anchor-coated or undercoated. The surface of the base film 1 to be coated (the surface on which the film is formed) may be subjected to corona treatment, low-temperature plasma treatment, atmospheric plasma treatment, or the like. This provides good wettability to the coating liquid and adhesive strength to the film.
[0022] The thickness of the base film 1 is appropriately selected according to the price and application, taking into consideration suitability as a packaging material and suitability for laminating other films. The thickness of the base film 1 is practically 3 μm to 200 μm, preferably 5 μm to 120 μm, and more preferably 10 μm to 100 μm.
[0023] The base film 1 may itself have heat sealability so that one or both outermost surfaces of the packaging material have heat sealability. Since the base film itself has heat sealability, the packaging material can be produced without laminating a sealant film or providing a sealant layer on the base film 1.
[0024] The deformation-resistant barrier coat layer 3A contains a hydroxyl group-containing polymer compound. Specific examples of the hydroxyl group-containing polymer compound include water-soluble polymers such as ethylene vinyl alcohol, polyvinyl alcohol, polyvinylpyrrolidone, and starch, and polyvinyl alcohol is particularly preferred because of its excellent barrier properties.
[0025] The thickness of the deformation-resistant barrier coat layer 3A is, for example, in the range of 0.05 μm to 2.0 μm, and may be, for example, 0.1 μm to 1 μm, or 0.2 μm to 6 μm. The thickness of the deformation-resistant barrier coat layer 3A is preferably set to a thickness that exhibits barrier properties and can reduce stress on the inorganic oxide layer described below.
[0026] The deformation-resistant barrier coat layer 3A may contain a hydroxyl group-containing polymeric compound and water-swellable mica. When the total mass of the deformation-resistant barrier coat layer 3A is taken as 100 parts by mass, the content of the water-swellable mica in the deformation-resistant barrier coat layer 3A is within the approximate range of, for example, 20 parts by mass to 50 parts by mass. The deformation-resistant barrier coat layer 3A can be formed using a coating liquid containing, as solid contents, a hydroxyl group-containing polymeric compound and water-swellable mica. The solid content ratio of the water-swellable mica in the total solid content of this coating liquid may be within the approximate range of, for example, 20% by mass to 50% by mass.
[0027] The area-average diameter of the water-swellable mica is, for example, within the approximate range of 0.5 μm to 5 μm, and may be within the approximate range of 1.5 μm to 2.5 μm. The aspect ratio of the water-swellable mica is, for example, within the approximate range of 10 to 200. The thickness of the deformation-resistant barrier coat layer 3A is, for example, within the approximate range of 0.1 μm to 1 μm, and may be within the approximate range of 0.15 μm to 0.7 μm.
[0028] The deformation-resistant barrier coat layer 3A may contain a composition containing at least one of a metal alkoxide, a hydrolysate thereof, and a polymer thereof, in addition to a hydroxyl group-containing polymer compound.
[0029] The metal alkoxide is preferably formed from a composition containing at least one selected from the group consisting of metal alkoxides represented by the following formula (1) and their hydrolysates or polymers. M(OR 1 ) m (R 2 ) n-m (1) In the above formula (1), R1 and R2 are each independently a monovalent organic group having 1 to 8 carbon atoms, and are preferably an alkyl group such as a methyl group or an ethyl group. M represents an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer from 1 to n.
[0030] Examples of metal alkoxides include tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-iso-C3H7)3], etc. Since the metal alkoxide is relatively stable in an aqueous solvent after hydrolysis, it is preferable to use tetraethoxysilane or triisopropoxyaluminum.
[0031] Examples of hydrolysates of metal alkoxides include silicic acid (Si(OH)4), which is a hydrolysate of tetraethoxysilane, and aluminum hydroxide (Al(OH)3), which is a hydrolysate of tripropoxyaluminum. These may be used alone or in combination of two or more. The content of the metal alkoxide and its hydrolysate in the composition is, for example, 10% by mass to 90% by mass.
[0032] The deformation-resistant barrier coat layer 3A may contain various additives within the range that does not impair the gas barrier property or strength as a packaging material. Examples of the additives include antioxidants, weathering agents, heat stabilizers, lubricants, crystal nucleating agents, ultraviolet absorbers, plasticizers, antistatic agents, colorants, fillers, surfactants, and silane coupling agents.
[0033] The deformation-resistant barrier coat layer 3A is formed by applying a coating liquid containing at least a water-soluble polymer as a constituent onto a substrate film by a known wet coating method, and then drying by heating.
[0034] [Second embodiment] Fig. 2 is a cross-sectional view showing a schematic configuration of a barrier film according to a second embodiment. The barrier film 10B shown in this figure differs from the barrier film 10A in that the barrier layer has a two-layer structure. That is, the barrier layer 2B is composed of a deformation-resistant barrier coat layer 3B and an inorganic oxide layer 4. The inorganic oxide layer 4 is disposed between the deformation-resistant barrier coat layer 3B and the base film 1. By forming the barrier layer 2B from the inorganic oxide layer 4 and the deformation-resistant barrier coat layer 3B in contact therewith, it is expected that the bending resistance and barrier properties of the barrier layer will be improved. When the barrier layer has a multi-layer structure, the deformation-resistant barrier coat layer is provided, for example, on the outermost side of the barrier layer.
[0035] When the barrier layer 2B includes the inorganic oxide layer 4, the deformation-resistant barrier coat layer 3B preferably has a smaller content of water-swellable mica than the deformation-resistant barrier coat layer 3A according to the first embodiment. That is, when the total mass of the deformation-resistant barrier coat layer 3B is 100 parts by mass, the content of water-swellable mica in the deformation-resistant barrier coat layer 3B is within the approximate range of, for example, 5 parts by mass to 35 parts by mass. This value may be 7 parts by mass or more, 10 parts by mass or more, or 12 parts by mass or more. This value may be 30 parts by mass or less, 20 parts by mass or less, or less than 20 parts by mass, or 17 parts by mass or less. In particular, this content may be in the range of less than 10 parts by mass and 20 parts by mass or less, or 15 parts by mass. The deformation-resistant barrier coat layer 3B can be formed using a coating liquid containing a hydroxyl group-containing polymer compound and water-swellable mica as solid contents. The solid content ratio of water-swellable mica among the total solid contents of this coating liquid may be adjusted to be in a desired range.
[0036] When the content of water-swellable mica in the deformation-resistant barrier coat layer 3B is equal to or greater than the lower limit, the labyrinth effect of the water-swellable mica provides excellent gas barrier properties and excellent moisture resistance to the deformation-resistant barrier coat layer 3B. On the other hand, when the content of water-swellable mica is equal to or less than the upper limit, the deformation-resistant barrier coat layer 3B can follow the deformation of the base film 1, so that the inorganic oxide layer 4 can be stably protected and excellent abuse resistance can be provided. Furthermore, when the content of water-swellable mica is within the above range, excellent adhesion strength between the inorganic oxide layer 4 and the deformation-resistant barrier coat layer 3B is achieved.
[0037] The thickness and other properties (excluding the content of water-swellable mica) of the deformation-resistant barrier coat layer 3B may be similar to those of the deformation-resistant barrier coat layer 3A.
[0038] By including the inorganic oxide layer 4 in the barrier layer 2B, it is possible to further improve the barrier properties against oxygen and water vapor. The inorganic oxide layer 4 includes a metal oxide, and examples of the metal oxide include oxides of metals such as aluminum, copper, silver, yttrium, tantalum, silicon, and magnesium. As the metal oxide, aluminum oxide and silicon oxide are preferable because they are inexpensive and have excellent barrier properties, and silicon oxide, which has particularly good water vapor barrier properties, is particularly preferable. Silicon oxide may have a composition SiOx, where x is 1.0 to 2.0. When x is 1.0 or more, good gas barrier properties tend to be easily obtained.
[0039] The inorganic oxide layer 4 is preferably formed by vacuum deposition. Examples of vacuum deposition include physical vapor deposition and chemical vapor deposition. Examples of physical vapor deposition include deposition, sputtering, and ion plating. Examples of chemical vapor deposition include thermal CVD, plasma CVD, and photo CVD.
[0040] The thickness of the inorganic oxide layer 4 is preferably 10 nm to 300 nm, and more preferably 20 nm to 100 nm. When the thickness of the inorganic oxide layer 4 is 10 nm or more, a uniform film tends to be easily obtained and gas barrier properties tend to be easily obtained. On the other hand, when the thickness of the inorganic oxide layer is 300 nm or less, flexibility can be maintained and cracks due to external forces such as bending and tension after film formation tend to be less likely to occur.
[0041] [Third embodiment] 3 is a cross-sectional view showing a schematic configuration of a barrier film according to a third embodiment. The barrier film 10C shown in this figure differs from the barrier film 10B in that an adhesion improving layer 5 is provided between the barrier layer 2B and the base film 1. The adhesion improving layer 5 is a layer that improves the adhesion of the barrier layer 2B to the base film 1. In particular, when the adhesion improving layer 5 is configured to be in contact with the inorganic oxide layer 4, the surface on which the inorganic oxide layer 4 is formed is planarized by the adhesion improving layer 5, and therefore further improvement in the barrier property is expected.
[0042] The material constituting the adhesion improving layer 5 is preferably selected from, for example, a solvent-soluble or water-soluble polyester resin, an isocyanate resin, a urethane resin, an acrylic resin, a vinyl alcohol resin, an ethylene vinyl alcohol resin, a vinyl modified resin, an epoxy resin, an oxazoline group-containing resin, a modified styrene resin, a modified silicone resin, an alkyl titanate, etc. These can be used alone or in combination of two or more kinds.
[0043] The adhesion improving layer 5 can be formed by a known printing method such as offset printing, gravure printing, silk screen printing, or a known coating method such as roll coating, knife edge coating, gravure coating. Drying conditions may be those generally used. In order to promote the reaction, a method of drying by leaving it in a high-temperature aging chamber for several days may be used. The thickness of the adhesion improving layer 5 is, for example, in the range of 0.01 μm to 1.0 μm.
[0044] [Fourth embodiment] 4 is a cross-sectional view showing a schematic configuration of a barrier film according to a fourth embodiment. The barrier film 10D shown in this figure includes at least a base film 11 and a barrier layer 12 provided on one surface of the base film 11. The barrier layer 12 includes at least an inorganic oxide layer 14 and a deformation-resistant barrier coat layer 13 provided in contact with the inorganic oxide layer 14. The configurations of the above-mentioned embodiments can be used for each component of the barrier film 10D, unless there is a contradiction.
[0045] The base film 11 is made of a plastic material. Examples of base films made of a plastic material include films made of polyolefin resins such as polyethylene, polypropylene, and propylene-ethylene copolymers, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyamide resins such as aliphatic polyamides such as nylon 6 and nylon 66, aromatic polyamides such as polymetaxylylene adipamide, vinyl resins such as polystyrene, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyvinyl alcohol, and ethylene-vinyl alcohol copolymer, acrylic resins such as homopolymers or copolymers of (meth)acrylic monomers such as polymethyl methacrylate and polyacrylonitrile, and cellophane. These resins are used alone or in combination of two or more.
[0046] Among these, polyolefin resin films (particularly, polypropylene films, etc.), polyester resin films (particularly, polyethylene terephthalate resin films), and polyamide resin films (particularly, nylon films) are preferably used as the base film 11.
[0047] A single-layer film made of a single resin or a single-layer or laminate film made of multiple resins is used as the base film 11. A laminate base material in which these resins are laminated on other base materials (metal, wood, paper, ceramics, etc.) may also be used.
[0048] The base film 11 may be an unstretched film, a uniaxially stretched or biaxially stretched oriented film, or a film that has been surface-treated (such as corona discharge treatment) or has been treated with an anchor coat or undercoat. By subjecting the surface of the base film 11 to be coated (the surface on which the film is formed) to corona treatment, low-temperature plasma treatment, atmospheric pressure plasma treatment, or the like, good wettability to the coating liquid and adhesive strength to the film can be obtained.
[0049] The thickness of the base film 11 is not particularly limited, and is appropriately selected according to the price and application, taking into consideration suitability as a packaging material and suitability for laminating other films. The thickness of the base film is practically 3 μm to 200 μm, preferably 5 μm to 120 μm, and more preferably 10 μm to 100 μm.
[0050] The base film 11 may itself have heat sealability so that one or both outermost surfaces of the packaging material have heat sealability. Since the base film itself has heat sealability, the packaging material can be produced without laminating a sealant film or providing a sealant layer on the base film.
[0051] The inorganic oxide layer 14 may be the same as the inorganic oxide layer 4 in the above embodiment.
[0052] The deformation-resistant barrier coat layer 13 contains at least a water-soluble polymer (a hydroxyl group-containing polymer compound) and water-swellable mica. By providing the deformation-resistant barrier coat layer 13 in contact with the surface of the inorganic oxide layer 14 opposite the substrate, even if the substrate film 11 is deformed by heat or the like, the deformation-resistant barrier coat layer 13 compensates for the barrier property of the inorganic oxide layer 14, thereby making it possible to maintain the barrier property.
[0053] [Water-soluble polymer] Water-soluble polymers are polymers that can be completely dissolved or finely dispersed in water at a specific temperature. Water-soluble polymers are not particularly limited as long as they are compounds that can penetrate and coordinate (intercalate) between unit crystal layers of inorganic layered minerals described later, and examples thereof include polyvinyl alcohol and its derivatives, cellulose derivatives such as carboxymethyl cellulose and hydroxyethyl cellulose, starches such as oxidized starch, etherified starch, and dextrin, polyvinylpyrrolidone, polyacrylic acid, and polymethacrylic acid or their esters, salts, and copolymers thereof, copolymerized polyesters containing polar groups such as sulfoisophthalic acid, vinyl polymers such as polyhydroxyethyl methacrylate and its copolymers, urethane polymers, or functional group-modified polymers such as carboxyl groups of these various polymers.
[0054] The water-soluble polymer is, for example, a polyvinyl alcohol resin having a saponification degree of 95% or more. The higher the saponification degree or polymerization degree of the polyvinyl alcohol resin, the lower the moisture absorption swelling property tends to be. When the saponification degree is 95% or more, sufficient gas barrier property is easily obtained.
[0055] When the water-soluble polymer is a polyvinyl alcohol resin, at least one of the polyvinyl alcohol resins may be a polyvinyl alcohol-based polymer or a derivative thereof.
[0056] The degree of polymerization of the polyvinyl alcohol resin is, for example, from 1100 to 2300, and may be from 1500 to 2000. When the degree of polymerization of the polyvinyl alcohol resin is within the above range, a film having improved gas barrier properties and cohesive strength of the coating layer can be obtained.
[0057] [Water-swellable mica] Mica is a type of inorganic layered mineral in which extremely thin unit crystal layers overlap to form a layered particle. Micas include natural mica and synthetic mica. Examples include muscovite, phlogopite, biotite, potassium phlogopite, potassium tetrasilicic mica, potassium taeniolite, potassium fluortetrasilicic mica, sodium fluortetrasilicic mica, sodium phlogopite, sodium tetrasilicic mica, sodium hectorite, etc. For the purpose of the present invention, one type of mica can be used, or two or more different types of mica can be combined together.
[0058] As the mica, those that swell and cleave in water are preferred, and among these, water-swellable mica that has swelling properties in water is particularly preferred. More specifically, it is a synthetic mica that has the property of absorbing and swelling water by coordinating it between the extremely thin unit crystal layers, and generally contains Si 4+ O 2- The layers are coordinated to form a tetrahedral structure, and the Al 3+ , Mg 2+ , Fe 2+ , and Fe 3+ Etc., O 2- and OH - The layers that form the octahedral structure are bonded to each other in a 1:1 or 2:1 ratio, and stacked to form a layered structure. For example, sodium tetrasilicic fluoride mica is preferable.
[0059] With regard to the size of the water-swellable mica, from the viewpoint that a high aspect ratio improves the barrier properties of the film, the aspect ratio of the water-swellable mica is, for example, 10 to 200, and may be 50 to 150. When the aspect ratio of the water-swellable mica is within the above range, it is highly likely that a film with improved gas barrier properties can be obtained, and at the same time, a decrease in the cohesive strength of the coating layer and the adhesive strength of the coating layer to the substrate can be prevented.
[0060] The area-average diameter (MA) of the water-swellable mica is, for example, 0.5 μm to 5 μm, or may be 1 μm to 3 μm, or may be 1.5 μm to 2.5 μm. The area-average diameter is the average particle diameter weighted by area. When the area-average diameter of the water-swellable mica is within the above range, the water-swellable mica is more uniformly dispersed in the coating layer without precipitating, and a film with maintained or improved gas barrier properties and transparency can be obtained.
[0061] When water-swellable synthetic mica is used as the water-swellable mica, the water-swellable synthetic mica has high compatibility with water-soluble polymers and contains fewer impurities than natural mica, so there is no decrease in gas barrier properties due to impurities and no decrease in the cohesive strength of the deformation-resistant barrier coat layer. Although not limited by a specific mechanism, water-swellable synthetic mica has fluorine atoms in its crystal structure, which is thought to contribute to reducing the humidity dependency of the gas barrier properties of the deformation-resistant barrier coat layer. Furthermore, since it has a high aspect ratio compared to other water-swellable inorganic layered minerals, the maze effect works more effectively, and in particular contributes to the high expression of the gas barrier properties of the coating layer.
[0062] In particular, when the water-soluble polymer is a polyvinyl alcohol resin, the water-swellable synthetic mica has high compatibility with the polyvinyl alcohol resin. In addition, when the area average diameter of the water-swellable synthetic mica is, for example, 0.5 μm to 5 μm, further 1 μm to 3 μm, or 1.5 μm to 2.5 μm, the water-swellable synthetic mica has higher compatibility with the polyvinyl alcohol resin.
[0063] When the water-swellable synthetic mica has a higher compatibility with the polyvinyl alcohol resin, a polyvinyl alcohol with a higher degree of polymerization can be used. By using a polyvinyl alcohol with a higher degree of polymerization, a film with improved gas barrier properties can be obtained. Specifically, when the area average diameter of the water-swellable synthetic mica is, for example, 0.5 μm to 5 μm, further 1 μm to 3 μm, or 1.5 μm to 2.5 μm, the polymerization degree of the polyvinyl alcohol can be 1100 or more, and a film with improved gas barrier properties can be obtained.
[0064] When the total mass of the deformation-resistant barrier coat layer 13 is 100 parts by mass, the content of the water-swellable mica in the deformation-resistant barrier coat layer 13 is, for example, within the approximate range of 5 parts by mass to 35 parts by mass. This value may be 7 parts by mass or more, 10 parts by mass or more, or 12 parts by mass or more. This value may be 30 parts by mass or less, 20 parts by mass or less, or less than 20 parts by mass, or 17 parts by mass or less. In particular, this content may be in the range of 10 parts by mass or more and less than 20 parts by mass, or 15 parts by mass. The deformation-resistant barrier coat layer 13 can be formed using a coating liquid containing a hydroxyl group-containing polymer compound and water-swellable mica as solid contents. The solid content ratio of the water-swellable mica among the total solid contents of the coating liquid may be adjusted to be within a desired range.
[0065] When the content of water-swellable mica in the deformation-resistant barrier coat layer 13 is equal to or greater than the lower limit, the labyrinth effect of the water-swellable mica provides excellent gas barrier properties and excellent moisture resistance to the deformation-resistant barrier coat layer 3B. On the other hand, when the content of water-swellable mica is equal to or less than the upper limit, the deformation-resistant barrier coat layer 13 can follow the deformation of the base film 11, so that the inorganic oxide layer 14 can be stably protected and excellent abuse resistance is provided. Furthermore, when the content of water-swellable mica is within the above range, excellent adhesion strength between the inorganic oxide layer 14 and the deformation-resistant barrier coat layer 13 is achieved.
[0066] The deformation-resistant barrier coat layer 13 can be formed by a known wet coating method. For example, the deformation-resistant barrier coat layer 13 is formed by applying a coating liquid containing at least a water-soluble polymer and water-swellable mica as main components, and then drying and removing the solvent component.
[0067] The coating liquid may contain water as a main solvent, or a solvent that dissolves in water or is uniformly mixed therein, such as alcohols, such as methanol, ethanol, and isopropanol, ketones, such as acetone and methyl ethyl ketone, ethers, such as tetrahydrofuran, cellosolves, carbitols, and nitriles, such as acetonitrile.
[0068] The wet coating method used includes roll coating, gravure coating, reverse coating, die coating, screen printing, spray coating, etc. Using these wet coating methods, a coating liquid is applied to one or both sides of a substrate film. As a method for drying the coating film, a known drying method such as hot air drying, hot roll drying, and infrared irradiation is used.
[0069] The thickness of the deformation-resistant barrier coat layer formed on the inorganic oxide layer 14 may be, for example, 0.1 μm to 1 μm, 0.15 μm to 0.7 μm, or 0.2 μm to 0.5 μm. If the thickness of the deformation-resistant barrier coat layer is 0.1 μm or more, sufficient gas barrier properties are likely to be obtained. On the other hand, if the thickness of the deformation-resistant barrier coat layer exceeds 1 μm, not only is it difficult to provide a uniform coating surface, but it also undesirably leads to an increase in drying load and an increase in production costs.
[0070] The thickness of the deformation-resistant barrier coat layer formed on the inorganic oxide layer 14 can be made thinner while maintaining sufficient barrier properties by adjusting the average particle size of the water-swellable mica contained in the deformation-resistant barrier coat layer. This is because the water-swellable mica is more uniformly dispersed in the deformation-resistant barrier coat layer by adjusting the average particle size of the water-swellable mica contained in the deformation-resistant barrier coat layer. For example, when the area-average diameter of the water-swellable mica is set in the range of 0.5 μm to 5 μm, or the range of 1 μm to 3 μm, or the range of 1.5 μm to 2.5 μm, the thickness of the deformation-resistant barrier coat layer can be made 1 μm or less while maintaining sufficient barrier properties.
[0071] The deformation-resistant barrier coat layer 13 may contain various additives within a range that does not impair the gas barrier properties or strength as a packaging material. Examples of the additives include antioxidants, weathering agents, heat stabilizers, lubricants, crystal nucleating agents, ultraviolet absorbers, plasticizers, antistatic agents, colorants, fillers, surfactants, and silane coupling agents.
[0072] An adhesion improving layer 5 (see FIG. 3) may be provided between the inorganic oxide layer 14 and the base film 11. The surface on which the inorganic oxide layer 4 is formed is flattened by the adhesion improving layer 5, which is expected to further improve the barrier property.
[0073] <Barrier packaging materials> 5 is a cross-sectional view showing a schematic configuration of a packaging material according to this embodiment. The packaging material 100 comprises a barrier film 10, an adhesive layer 20, and a sealant layer 30, in this order. The barrier film 10 comprises a base film 1 and a barrier layer 2. The adhesive layer 20 is provided between the barrier layer 2 of the barrier film 10 and the sealant layer 30. An ink layer 40 is provided on the surface of the barrier layer 2 (the surface opposite to the side of the base film 1).
[0074] The barrier film 10 has a configuration similar to that of any one of the barrier films 10A to 10D according to the above embodiments, for example.
[0075] The adhesive constituting the adhesive layer 20 may be an acrylic, polyester, ethylene-vinyl acetate, urethane, vinyl chloride-vinyl acetate, chlorinated polypropylene, or other adhesive, depending on the material of each layer to be laminated. A solvent-free adhesive may also be used. The adhesive layer 20 may be formed using, for example, a roll coater, reverse roll coater, gravure coater, microgravure coater, knife coater, bar coater, wire bar coater, die coater, dip coater, or the like. The amount of adhesive applied may be, for example, 1 g / m. 2 ~10g / m 2 It is.
[0076] The sealant layer 30 functions as an adhesive when packaging the contents using a packaging material. Examples of materials constituting the sealant layer 30 include unstretched polyethylene film and unstretched polypropylene film. The thickness of the sealant layer 30 is, for example, 15 μm to 200 μm.
[0077] The sealant layer 30 is preferably made of the same plastic material as the base film 1. For example, when the base film 1 is a polyethylene film, the sealant layer 30 is preferably made of a polyethylene film, and when the base film 1 is a polypropylene film, the sealant layer 30 is preferably made of a polypropylene film. polypropylene It is preferable that the base film 1 and the sealant layer 30 are made of the same plastic material. Here, the same plastic material means that the main plastic material constituting the base film 1 and the sealant layer 30 is the same, and that they can be recycled in the same recycling process. If they can be recycled in the same recycling process, they may contain other different components. If the two base films are made of the same plastic material, it is possible to make them recyclable as packaging materials. The sealant layer 30 may contain a resin material derived from biomass or recycled.
[0078] The ink layer 40 is a layer on which characters, patterns, etc. are formed for practical use as a packaging bag, etc. For example, it is a layer constituted by an ink made by adding various pigments, extender pigments, and additives such as plasticizers, drying agents, stabilizers, etc. to an ink binder resin such as a urethane-based, acrylic-based, nitrocellulose-based, rubber-based, or vinyl chloride-based ink. Biomass ink or flexographic ink may be used as the ink. The ink layer 40 may be provided on the surface of the base film 1.
[0079] The oxygen permeability of the barrier film 10 is, for example, 10 cm 3 / m 2 ·day·atm or less, 5cm 3 / m 2 The water vapor permeability of the barrier film 10 can be, for example, 3 g / m 2 -day or less, 1.5g / m 2 ·day or less.
[0080] The oxygen permeability of the packaging material 100 is, for example, 10 cm 3 / m 2 ·day·atm or less, 5cm 3 / m 2 The water vapor permeability of the packaging material 100 can be, for example, 5 g / m 2 -day or less, 1.5g / m 2 The packaging material 100 can be used, for example, as flexible packaging for dry contents, liquid contents, food, and non-food items.
[0081] The peel strength (lamination strength) of the barrier film 10 may be 1 N / 15 mm or more, or may be 2 N / 15 mm or more. This peel strength is the peel strength when the surface of the barrier film 10 on the barrier layer 2 side is bonded to the sealant layer 30 (or other plastic film) via the adhesive layer 20. This peel strength means a value measured according to the T-peel peel adhesion strength test method (JIS K6854-3, ISO11339) or the 180-degree peel peel adhesion strength test method (JIS K6854-2, ISO8510-2). The measurement sample may be prepared by cutting a laminate including the barrier film 10 into a 15 mm-wide strip.
[0082] The heat seal strength when the sealant layers 30 of the packaging material 100 are heat sealed together may be 15 N / 15 mm or more, or may be 30 N / 15 mm or more. This heat seal strength refers to a value measured according to a T-peel peel adhesion strength test method (JIS K6854-3, ISO11339). A measurement sample may be prepared by cutting a laminate including the heat-sealed packaging material 100 into a 15 mm-wide strip. EXAMPLES
[0083] The present disclosure will be described below based on examples and comparative examples. The present invention is not limited to the following examples.
[0084] <Base film> Films A to C containing polyethylene were prepared. · Film A: MD oriented film with a core layer of HDPE and MDPE laminated on both sides. · Film B: MD oriented film made of HDPE. · Film C: Unstretched film made of HDPE. Table 1 shows the thickness and heat shrinkage rate of films A to C.
[0085] [Table 1]
[0086] <Preparation of deformation-resistant barrier coat layer> The following solution was prepared as a coating liquid for the deformation-resistant barrier coat layer. Polyvinyl alcohol resin (PVA, Selvol-325 (saponification degree 98-99%, polymerization degree 1700), manufactured by Sekisui Specialty Chemicals America, LLC.) was used as the hydroxyl group-containing polymer compound. The polyvinyl alcohol resin and water were mixed and heated at 95°C to dissolve the polyvinyl alcohol resin in water. After cooling the mixture to room temperature, it was diluted with water and isopropanol (mass ratio 1:1) so that the final solid concentration was 5 mass% to prepare component (A).
[0087] Water-swellable synthetic mica (Somasif MEB-3, manufactured by Co-op Agri Co., Ltd.) was used as the water-swellable mica. The water-swellable synthetic mica was treated using a bead mill so that the area particle size was 2 μm. Then, water was mixed so that the final solid concentration was 8 mass %, and component (B) was prepared.
[0088] Components (A) and (B) were diluted with water and methanol (mass ratio 1:1) so that the content of water-swellable synthetic mica in the final deformation-resistant barrier coat layer was 15 mass %, to prepare deformation-resistant barrier coat layer coating solution A.
[0089] Components (A) and (B) were diluted with water and methanol (mass ratio 1:1) so that the content of water-swellable synthetic mica in the final deformation-resistant barrier coat layer was 35 mass %, to prepare deformation-resistant barrier coat layer coating solution B.
[0090] Components (A) and (B) were diluted with water and methanol (mass ratio 1:1) so that the content of water-swellable synthetic mica in the final deformation-resistant barrier coat layer was 25 mass %, to prepare deformation-resistant barrier coat layer coating solution C.
[0091] Components (A) and (B) were diluted with water and methanol (mass ratio 1:1) so that the content of water-swellable synthetic mica in the final deformation-resistant barrier coat layer was 22.5 mass %, to prepare deformation-resistant barrier coat layer coating solution D.
[0092] Components (A) and (B) were diluted with water and methanol (mass ratio 1:1) so that the content of water-swellable synthetic mica in the final deformation-resistant barrier coat layer was 20 mass %, to prepare deformation-resistant barrier coat layer coating solution E.
[0093] Components (A) and (B) were diluted with water and methanol (mass ratio 1:1) so that the content of water-swellable synthetic mica in the final deformation-resistant barrier coat layer was 5 mass %, to prepare deformation-resistant barrier coat layer coating solution F.
[0094] The component (A) was diluted with water and methanol (mass ratio 1:1) to prepare a barrier coat layer coating solution G.
[0095] Components (A) and (B) were diluted with water and methanol (mass ratio 1:1) so that the content of water-swellable synthetic mica in the final deformation-resistant barrier coat layer was 40 mass %, to prepare barrier coat layer coating solution H.
[0096] The components (A) and (B), as well as the silane coupling agent and tetraethoxysilane, were diluted with water and methanol (mass ratio 1:1) to prepare a barrier coat layer coating liquid I having the following composition. ·PVA: 30.5 parts by mass ·Water-swellable synthetic mica: 2.1 parts by mass Silane coupling agent: 4.4 parts by weight Tetraethoxysilane: 63.0 parts by weight
[0097] <Preparation of Barrier Film> Example 1 A coating solution for forming an adhesive layer containing an acrylic polyol, an isocyanate compound, and an epoxy-based silane coupling agent was applied onto film A and dried by heating. The coating amount after drying was 0.1 g / m2 Silicon oxide (SiOx, x=1.8) was vapor-deposited on the surface on which the adhesion improving layer was to be formed, to form an inorganic oxide layer having a thickness of 0.03 μm.
[0098] The coating liquid A for the deformation-resistant barrier coat layer was applied onto the inorganic oxide layer by gravure coating and dried, thereby obtaining a barrier film provided with a deformation-resistant barrier coat layer (thickness: 0.3 μm).
[0099] Example 2 The barrier film of Example 2 was produced in the same manner as in Example 1, except that the amount of coating liquid for the deformation-resistant barrier coat layer was changed to make the thickness of the deformation-resistant barrier coat layer 0.6 μm.
[0100] Example 3 A barrier film of Example 3 was produced in the same manner as in Example 1, except that the base film was changed to Film A.
[0101] Example 4 The barrier film of Example 4 was produced in the same manner as in Example 3, except that the amount of coating liquid for the deformation-resistant barrier coat layer was changed to make the thickness of the deformation-resistant barrier coat layer 0.6 μm.
[0102] Example 5 A barrier film of Example 5 was produced in the same manner as in Example 1, except that the base film was changed to Film C.
[0103] Example 6 The barrier film of Example 6 was produced in the same manner as in Example 5, except that the amount of coating liquid for the deformation-resistant barrier coat layer was changed to make the thickness of the deformation-resistant barrier coat layer 0.6 μm.
[0104] Example 7 Onto the film C, the coating liquid B for the deformation-resistant barrier coat layer was applied by gravure coating and dried to form a deformation-resistant barrier coat layer having a thickness of 0.3 μm, thereby producing the barrier film of Example 7.
[0105] <Evaluation of Barrier Films According to Examples 1 to 7> [Oxygen permeability measurement (isobaric method)] Oxygen permeability (cm) at 30℃ and 70% RH 3 / m 2 The oxygen permeability of the gas barrier film was measured using an oxygen permeability measuring device MOCON (OX-TRAN2 / 21, manufactured by Modern Controls). The results of measuring the oxygen permeability of the gas barrier film are shown in Table 2.
[0106] [Measurement of water vapor permeability] Water vapor permeability (g / m2) at 40℃ and 90%RH 2 ·day) was measured using a water vapor transmission rate measuring device PERMATRAN W-3 / 33 MG (Modern Controls, Inc.) The results of measuring the water vapor transmission rate of the gas barrier film are shown in Table 2.
[0107] [Measurement of heat shrinkage rate] A letter-sized sample (8.5in x 11in = 215.9mm x 279.4mm) was cut out from the base film, and seven plots were made, two points each parallel to TD and MD, as shown in Figure 6 (the intervals between Tn-Tn' and Mn-Mn' were both 10mm). The film was placed on a glass plate without being fixed, and the oven was set to the heating temperature in Table 1 and heated in the oven for 15 minutes. The distances between Tn-Tn' and Mn-Mn' of the removed film were measured, and Tn-Tn' (after heating) / Tn-Tn' (before heating) and Mn-Mn' (after heating) / Mn-Mn' (before heating) were taken as the thermal shrinkage rates in TD and MD, respectively.
[0108] [Laminate strength measurement] A 60 μm thick LLDPE (Linear Low Density Polyethylene) film was laminated onto the barrier films of Examples 1 to 7 to prepare a barrier packaging material. This barrier packaging material was prepared by laminating an LLDPE film with a polyester urethane adhesive (Takelac A-525, manufactured by Mitsui Chemicals, Inc. / Takenate A-52, manufactured by Mitsui Chemicals, Inc.) by dry lamination processing so that the LLDPE film and the deformation-resistant barrier coat layer faced each other, and aging (aging) at 40° C. for 48 hours. This packaging material was cut into a 15 mm wide strip, and the gas barrier film was peeled off at a speed of 300 mm / min using a Tensilon universal material testing machine (manufactured by A&D Co., Ltd.) to measure the laminate strength. The measurements were performed according to the T-peel peel adhesion strength test method (JIS K6854-3, ISO11339) and the 180-degree peel peel adhesion strength test method (JIS K6854-2, ISO8510-2). The results are shown in Table 2. In all cases, the peel interface was confirmed between the substrate film and the deformation-resistant barrier coat layer.
[0109] [Table 2]
[0110] <Evaluation of the barrier packaging materials according to Examples 1 and 7> [Heat seal strength] Two sheets of each of the barrier packaging materials according to Examples 1 and 7 were prepared. The two sheets of the barrier packaging material were overlapped with the sealant layers facing each other, and heat sealed using a heat sealer under conditions of 160°C, 0.2 MPa, and 1 second. The heat-sealed sample was cut into a 15 mm-wide strip, and heat-seal strength was measured according to the "Heat-seal strength test for bags" described in JIS Z0238:1998. The heat-seal strength was measured using a Tensilon universal material testing machine (manufactured by A&D Co., Ltd.) at a tensile speed of 300 mm / min. The results are shown in Table 3.
[0111] [Oxygen permeability measurement (isobaric method)] Oxygen permeability (cm) at 30℃ and 70% RH 3 / m 2 The oxygen permeability of the gas barrier film was measured using an oxygen permeability measuring device MOCON (OX-TRAN2 / 21, manufactured by Modern Controls). The results of measuring the oxygen permeability of the gas barrier film are shown in the "After Lamination" section of Table 3.
[0112] [Measurement of water vapor permeability] Water vapor permeability (g / m2) at 40℃ and 90%RH 2 ·day) was measured using a water vapor transmission rate measuring device PERMATRAN W-3 / 33 MG (Modern Controls). The results of measuring the water vapor transmission rate of the barrier packaging materials are shown in the "After Lamination" section of Table 3.
[0113] [Abuse Test] The barrier packaging materials according to Examples 1 and 7 were cut into samples measuring 295 mm long x 210 mm wide. The following abuse test was carried out on these samples. That is, the samples were attached to the fixed head of a Gelbo Flex Tester manufactured by Tester Sangyo Co., Ltd. in a cylindrical shape with a diameter of 87.5 mm x 210 mm. Both ends of the sample were held, the initial gripping distance was set to 175 mm, and a 440° twist was applied with a stroke of 87.5 mm. This action was repeated 50 times at a speed of 40 times / min to bend the sample. The oxygen permeability and water vapor permeability of the samples after the abuse test were measured by the above method. The results are shown in the "After Abuse Test" section of Table 3.
[0114] [Table 3]
[0115] Example 8 The barrier film of Example 8 was produced in the same manner as in Example 1, except that the base film was changed to a biaxially oriented polypropylene film (PP, thickness 20 μm, manufactured by Polo Films) and the coating liquid B for the deformation-resistant barrier coat layer was used instead of the coating liquid A for the deformation-resistant barrier coat layer.
[0116] Example 9 The barrier film of Example 9 was produced in the same manner as in Example 8, except that Coating Liquid C for the deformation-resistant barrier coat layer was used instead of Coating Liquid B for the deformation-resistant barrier coat layer.
[0117] Example 10 The barrier film of Example 10 was produced in the same manner as in Example 8, except that Coating Liquid D for the deformation-resistant barrier coat layer was used instead of Coating Liquid B for the deformation-resistant barrier coat layer.
[0118] Example 11 The barrier film of Example 11 was produced in the same manner as in Example 8, except that Coating Liquid E for the deformation-resistant barrier coat layer was used instead of Coating Liquid B for the deformation-resistant barrier coat layer.
[0119] Example 12 The barrier film of Example 12 was produced in the same manner as in Example 8, except that Coating Liquid A for the deformation-resistant barrier coat layer was used instead of Coating Liquid B for the deformation-resistant barrier coat layer.
[0120] (Example 13) The barrier film of Example 13 was produced in the same manner as in Example 8, except that Coating Liquid F for the deformation-resistant barrier coat layer was used instead of Coating Liquid B for the deformation-resistant barrier coat layer.
[0121] Comparative Example 1 A barrier film of Comparative Example 1 was produced in the same manner as in Example 8, except that Coating Liquid G for the Barrier Coat Layer was used instead of Coating Liquid B for the Deformation-Resistant Barrier Coat Layer.
[0122] Comparative Example 2 A barrier film of Comparative Example 2 was produced in the same manner as in Example 8, except that the coating solution H for the barrier coat layer was used instead of the coating solution B for the deformation-resistant barrier coat layer.
[0123] Comparative Example 3 A barrier film of Comparative Example 3 was produced in the same manner as in Example 8, except that the coating liquid I for the barrier coat layer was used instead of the coating liquid B for the deformation-resistant barrier coat layer.
[0124] <Preparation of barrier packaging materials> A 30 μm thick unstretched polypropylene film (CPP GLC, manufactured by Mitsui Chemicals Tocello Co., Ltd.) was used as a sealant. layer The barrier films of Examples 8 to 13 and Comparative Examples 1 to 3 were dry-laminated on the barrier layer-forming surface (barrier coat layer surface) of each gas barrier film with a polyester urethane adhesive (Takelac A-525, manufactured by Mitsui Chemicals, Inc. / Takenate A-52, manufactured by Mitsui Chemicals, Inc.) interposed therebetween, so that the deformation-resistant barrier coat layer surface and the sealant layer faced each other. layer The resulting material was aged at 40° C. for 48 hours to obtain barrier packaging materials of Examples 8 to 13 and Comparative Examples 1 to 3.
[0125] <Evaluation of Barrier Films According to Examples 8 to 13> [Evaluation of oxygen permeability and water vapor permeability of barrier films] For the barrier films of Examples 8 to 13, oxygen permeability and water vapor permeability were measured in the same manner as in Examples 1 to 7. The results are shown in the "Before lamination" section of Table 4. In addition, for the barrier packaging materials of Examples 8 to 13, oxygen permeability and water vapor permeability were measured in the same manner as in Examples 1 to 7. The results are shown in the "After lamination" section of Table 4.
[0126] [Evaluation of bending resistance] The barrier packaging materials according to Examples 8 to 13 were cut into samples measuring 295 mm long x 210 mm wide. These samples were subjected to the same abuse test as described above. The oxygen permeability and water vapor permeability of the samples after the abuse test were measured by the above-mentioned method. The results are shown in the "After Abuse Test" section of Table 4.
[0127] [Laminate strength measurement] The barrier packaging materials according to Examples 8 to 13 were cut into strips of 15 mm width, and the gas barrier film and the sealant were measured using a Tensilon universal material testing machine (manufactured by A&D Co., Ltd.). layerThe laminate strength was measured by peeling at an angle of 90° at the interface with the substrate film at a speed of 300 mm / min. The measurement was performed according to the peel adhesion strength test method for T-type peeling (JIS K6854-3, ISO11339). The results are shown in Table 4. In Examples 8 to 11, the peel interface was confirmed between the substrate film and the deformation-resistant barrier coat layer. In Examples 12 and 13, the film broke during the measurement.
[0128] [Heat seal strength] Two sheets of each of the barrier packaging materials according to Examples 8 to 13 were prepared. The two sheets of the barrier packaging material were overlapped so that the sealant layers faced each other, and heat-sealed using a heat sealer under conditions of 160°C, 0.2 MPa, and 1 second. The heat-sealed sample was cut into a 15 mm-wide strip, and heat-seal strength was measured in accordance with the "Heat-seal strength test for bags" described in JIS Z0238:1998. The heat-seal strength was measured using a Tensilon universal material testing machine (manufactured by A&D Co., Ltd.) at a tensile speed of 300 mm / min. The results are shown in the "Heat-seal strength" section of Table 4. In Examples 8 to 11, the peel interface was confirmed between the substrate film and the deformation-resistant barrier coat layer. In Examples 12 and 13, the film broke during the measurement.
[0129] [Table 4] In the table, "-" means that the data was not measured.
[0130] <Evaluation of Barrier Films According to Comparative Examples 1 to 3> [Evaluation of oxygen permeability of barrier films] The oxygen permeability of the barrier films according to Comparative Examples 1 to 3 was measured in the same manner as in Examples 1 to 7. measurement The results are shown in the "Before lamination" section of Table 5.
[0131] [Evaluation of water vapor permeability of barrier films] For the barrier films of Comparative Examples 1 to 3, water vapor permeability was measured in the same manner as in Examples 1 to 7 (measured with the surface of the barrier coat layer facing the sensor side (humidity 0% side)). The results are shown in the "Before lamination 1" section of Table 4. For the barrier films of Comparative Examples 1 to 3, water vapor permeability was measured with the surface of the barrier coat layer facing the high humidity side (humidity 90% side). The results are shown in the "Before lamination 2" section of Table 4.
[0132] <Evaluation of Barrier Packaging Materials According to Comparative Examples 1 to 3> [Evaluation of oxygen permeability of barrier packaging materials] The oxygen permeability of the barrier packaging materials according to Comparative Examples 1 to 3 was measured in the same manner as in Examples 1 to 7. measurement The results are shown in the "Before lamination" section of Table 5.
[0133] [Evaluation of water vapor permeability of barrier packaging materials] For the barrier packaging materials according to Comparative Examples 1 to 3, the water vapor permeability was measured in the same manner as in Examples 1 to 7. The results are shown in Table 5 under the heading "After lamination."
[0134] [Evaluation of bending resistance] The barrier packaging materials according to Comparative Examples 1 to 3 were cut into samples measuring 295 mm long x 210 mm wide. These samples were subjected to the abuse test in the same manner as described above. The oxygen permeability and water vapor permeability of the samples after the abuse test were measured by the above-mentioned methods. The results are shown in the "After Abuse Test" section of Table 5.
[0135] [Laminate strength measurement] The barrier packaging materials according to Comparative Examples 1 to 3 were cut into strips with a width of 15 mm, and the T-peel strength and 180° peel strength were measured in the same manner as in Examples 1 to 7. The results are shown in Table 5.
[0136] [Heat seal strength] Two sheets of each of the barrier packaging materials according to Comparative Examples 1 to 3 were prepared. The two sheets of the barrier packaging materials were overlapped with the sealant layers facing each other, and heat sealed using a heat sealer under conditions of 160°C, 0.2 MPa, and 1 second. The heat-sealed sample was cut into a 15 mm-wide strip, and the heat seal strength was measured in the same manner as in Examples 1 and 7. The results are shown in Table 5.
[0137] [Table 5] In the table, "-" means that the data was not measured.
[0138] The barrier film of Comparative Example 1, in which the barrier coat layer did not contain water-swellable mica (inorganic layered mineral), had insufficient moisture resistance and was found to have a reduced barrier property (see 2 before lamination). The barrier film of Comparative Example 2, in which the content of water-swellable mica in the barrier coat layer was 40 mass %, had insufficient T-peel strength. [Industrial Applicability]
[0139] According to the present disclosure, there are provided a barrier film and a barrier packaging material that are useful for realizing excellent recyclability of packaging materials and have excellent gas barrier properties. [Explanation of symbols]
[0140] 1, 11...base film, 2, 2B, 12...barrier layer, 3A, 3B, 13...deformation-resistant barrier coat layer, 4, 14...inorganic oxide layer, 5...adhesion improving layer, 10, 10A, 10B, 10C, 10D...barrier film, 20...adhesive layer, 30...sealant layer, 40...ink layer, 100...barrier packaging material
Claims
1. A barrier packaging material comprising a barrier film and a sealant layer, The barrier film A base film; an inorganic oxide layer provided on one surface of the base film; a deformation-resistant barrier coat layer provided on and in contact with the inorganic oxide layer; Equipped with the deformation-resistant barrier coat layer comprises a hydroxyl group-containing polymer compound and water-swellable mica having an aspect ratio of 50 to 150; the content of the hydroxyl group-containing polymer compound in the deformation-resistant barrier coat layer is 65 parts by mass to 95 parts by mass and the content of the water-swellable mica in the deformation-resistant barrier coat layer is 5 parts by mass to 35 parts by mass, relative to 100 parts by mass of the total mass of the deformation-resistant barrier coat layer; A barrier packaging material, wherein the base film is a polyethylene film and the sealant layer is made of a polyethylene resin.
2. A barrier packaging material comprising a barrier film and a sealant layer, The barrier film A base film; an inorganic oxide layer provided on one surface of the base film; a deformation-resistant barrier coat layer provided on and in contact with the inorganic oxide layer; Equipped with the deformation-resistant barrier coat layer comprises a hydroxyl group-containing polymer compound and water-swellable mica having an aspect ratio of 50 to 150; the content of the hydroxyl group-containing polymer compound in the deformation-resistant barrier coat layer is 65 parts by mass to 95 parts by mass and the content of the water-swellable mica in the deformation-resistant barrier coat layer is 5 parts by mass to 35 parts by mass, relative to 100 parts by mass of the total mass of the deformation-resistant barrier coat layer; A barrier packaging material, wherein the base film is a polypropylene film and the sealant layer is made of a polypropylene resin.
3. 3. The barrier packaging material according to claim 1, wherein the content of the water-swellable mica in the deformation-resistant barrier coat layer is less than 20 parts by mass.
4. 4. The barrier packaging material according to claim 1, wherein the base film has a heat shrinkage rate of 2% or less at 100° C. for 15 minutes in a first direction on a film plane and in a second direction perpendicular to the first direction.
5. 5. The barrier packaging material according to claim 1, wherein the base film has a heat shrinkage rate of 5% or less at 120° C. for 15 minutes in a first direction on a film plane and in a second direction perpendicular to the first direction.
6. The barrier packaging material according to any one of claims 1 to 5, further comprising an adhesion improving layer between the base film and the inorganic oxide layer.
Citation Information
Patent Citations
Polyethylene composite film
JP1985230851A
Laminated film
JP1995251475A
Gas barrier film and manufacture thereof
JP1998166516A
Gas barrier laminate and its production and packaging material and package
JP1999334018A
Vapor-deposited film laminated packaging material
JP2000254994A
